已知:fn(x)=a1x+a2x2+…+anxn,fn(-1)=(-1)n•n,n=1,2,3,… (I)求a1、a2、a3; (II)求数列{an}的通项公式; (II)求证:fn(
|
由已知f1(-1)=-a1=-1,所以a1=1(1分)
f2(-1)=-a1+a2=2,所以a2=3,
f3(-1)=-a1+a2-a3=-3,所以a3=5(3分)
(II)∵(-1)n+1•an+1=fn+1(-1)-fn(-1)=(-1)n+1•(n+1)-(-1)n•n
∴an+1=(n+1)+n
即an+1=2n+1
所以对于任意的n=1,2,3,an=2n-1(7分)
(III)fn(x)=x+3x2+5x3++(2n-1)xn
∴fn(
)=1 3
+3(1 3
)2+5(1 3
)3+…+(2n-1)(1 3
)n ①1 3
fn(1 3
)=(1 3
)2+3(1 3
)3+5(1 3
)4+…+(2n-1)(1 3
)n+1 ②1 3
①─②,得
fn(2 3
)=(1 3
)+2(1 3
)3+2(1 3
)4+…+2(1 3
)n-(2n-1)(1 3
)n+1 (9分)1 3
=
+1 3
-(2n-1)(
[1-(2 9
)n-1]1 3 1- 1 3
)n+1=1 3
-2 3
(2n-2 3
)n1 3
∴fn(
)=1-1 3
,(12分)n-1 3n
又n=1,2,3,故fn(
)<1(13分)1 3